Investigation and analysis of the optical Kerr nonlinear effect caused by metal nanocomposite on the performance of nonlinear hybrid plasmonic waveguide. (18th June 2021) - Ghorbani, Saeed; Sadeghi, Mojtaba; Adelpour, Zahra
Abstract: In this paper, a nonlinear hybrid plasmonic waveguide (HPW) with a layer of metal-nanocomposite as nonlinear Kerr material with the high nonlinear response, long propagation length and tight light confinement for processing and active control of optical signals for nonlinear applications has been proposed. The effective parameters of the nonlinear layer due to third-order susceptibility in the HPW structure, which includes the nonlinear metal-nanocomposite layer, have been analyzed by using the Maxwell-Garnett theory. The presence of metal nanoparticles in the nanocomposite host medium improves the nonlinear effect of the proposed HPW structure. Also, the effect of radius, volume fraction, host medium permittivity related to nanoparticles and nanocomposite on the performance and output results of effective nonlinearity coefficient, propagation length, effective mode area, confinement factor has been simulated by using FEM numerical solution method in TM mode. The proposed nonlinear hybrid plasmonic waveguide is an ideal option for design and application in nonlinear all-optical integrated circuits.